Morphological variability in Illex coindetii (Cephalopoda: Ommastrephidae) along the north-west coast of Africa - Hernández-García, V.; Castro, J. J. (Journal of the Marine Biological Association of the United Kingdom, 1998)
This paper gives morphometric variations and dorsal mantle length-total weight (DML-TW) relationships for Illex coindetii in the eastern Central Atlantic area. Positive allometry was observed in males and negative in females of the species. The most variable body measurements between males and females were width and perimeter of the head. In the study area, divergence of morphometric measurement starts at 95 mm. The point of divergence, however, varies with latitude; fluctuating from 104 mm in the north (Morocco and Sahara) to 76 mm in the central area (Mauritania and north of Senegal) and 73 mm in the south (Gulf of Guinea). The relationships between DML and TW showed that sexual dimorphism due to differential growth between males and females starts to occur at 56 mm ML. The starting point of sexual dimorphism (56 mm) varies according to the zone; the higher the latitude, the later it occurs. Thus, sexual dimorphism occurs at 49 mm in the south (Gulf of Guinea), at 54 mm in the central area (Mauritania and north of Senegal) and at 74 mm in the north (Morocco and Sahara). Females grow larger than males, but males were heavier at any given length. As latitude decreased, a slow down in the increase in weight-at-length was observed in both sexes. 1268 1259 1,053 Q2 SCIE